Characterization of the lactococcal abiD1 gene coding for phage abortive infection. - Anba, J (1995)
Lactococcal phage abortive infection (AbiD1) determined by plasmid pIL105 is active on both prolate- and small-isometric-head phages of the C6A and 936 phage groups, respectively, which are considered two different species.The Abi phenotype was found to be encoded by a single gene, designated abiD1. The abiD1-encoded protein (351 amino acids) does not show homology with any known protein and has a deduced isoelectric point of 10. It also possesses two helix-turn-helix structures and an unusually high content of asparagine, isoleucine, and lysine. A consensual promoter with a TGy extension to the -10 box was mapped 76 bp upstream of the start codon. Transcription initiated at this strong promoter stops at a terminator located 48 bp downstream from the promoter. The termination process is very efficient, and transcripts corresponding to the abiD1 gene were not visible in our experimental conditions with or without phage infection. Expression of abiD1 under the control of a T7 promoter induced a lag phase in Lactococcus lactis cell growth, suggesting that overproduction of AbiD1 could be toxic for the cells. AbiD1 protein was visualized in Escherichia coli by using a tightly controlled expression system.